2019
DOI: 10.1093/schbul/sbz039
|View full text |Cite
|
Sign up to set email alerts
|

What Causes the Onset of Psychosis in Individuals at Clinical High Risk? A Meta-analysis of Risk and Protective Factors

Abstract: Twenty percent of individuals at clinical high risk for psychosis (CHR-P) develop the disorder within 2 years. Extensive research has explored the factors that differentiate those who develop psychosis and those who do not, but the results are conflicting. The current systematic review and meta-analysis comprehensively addresses the consistency and magnitude of evidence for non-purely genetic risk and protective factors associated with the risk of developing psychosis in CHR-P individuals. Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 65 publications
5
109
0
4
Order By: Relevance
“…Thus, this dynamic model appeared to be a better method for prediction of transition to psychosis in CHR. The second paper is one of the first and largest meta-analysis of both risk and protective factors that might predict transition 47 . Reviewing 128 studies and 26 potential risk factors, the authors identified the most robust risk factors for psychosis against different types of biases 48 , classifying the levels of evidence of the association as convincing (Class I), highly suggestive (Class II), suggestive (Class III) and not met or weak (Class IV).…”
Section: Current Issues With Predictionmentioning
confidence: 99%
“…Thus, this dynamic model appeared to be a better method for prediction of transition to psychosis in CHR. The second paper is one of the first and largest meta-analysis of both risk and protective factors that might predict transition 47 . Reviewing 128 studies and 26 potential risk factors, the authors identified the most robust risk factors for psychosis against different types of biases 48 , classifying the levels of evidence of the association as convincing (Class I), highly suggestive (Class II), suggestive (Class III) and not met or weak (Class IV).…”
Section: Current Issues With Predictionmentioning
confidence: 99%
“…Since that time, prospective studies have established the long-term consequences of pre-and perinatal hazards on exposed infants 24,25 . These, and also umbrella reviews 26 (meta-analyses of meta-analyses) have revealed that numerous pre-and perinatal risk factors are associated not only with psychosis but with a range of cognitive and neurological abnormalities as well as other psychiatric and neurodevelopmental disorders [27][28][29][30][31][32] ; neuroimaging studies have demonstrated that when such infants reach adulthood they show an excess of brain structural and dopaminergic abnormalities reminiscent of those found in patients with schizophrenia 25,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Имеются данные о том, что не только АПС, но и первичные негативные симптомы, возникающие на доманифестных этапах эндогенного процесса [17,35,36], ассоциированы с риском манифестации психоза [37]. Установлено, что они встречаются у 85% пациентов из группы КВР-П [38].…”
Section: полиморфизм группы квр-пunclassified